2017
DOI: 10.1161/atvbaha.117.309291
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell–Derived Endothelial Cells in Insulin Resistance and Metabolic Syndrome

Abstract: Insulin resistance leads to a number of metabolic and cellular abnormalities including endothelial dysfunction that increase the risk of vascular disease. Although it has been particularly challenging to study the genetic determinants that predispose to abnormal function of the endothelium in insulin resistant states, the possibility of deriving endothelial cells from induced pluripotent stem cells (iPSC-ECs) generated from individuals with detailed clinical phenotyping, including accurate measurements of insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(53 reference statements)
0
17
0
1
Order By: Relevance
“…Several studies have shown that these aberrant epigenetic changes may be partially overcome by genome-wide chemical treatments that restore some endothelial function 56,57 . The extent of retention of diseased diabetic epigenetic memory at developmental genes from incomplete or ineffective reprogramming within DhiPSC-derived lineages and its role in impaired regenerative capacity remains unclear, and marked by high variability in differentiation efficiency or retention of diseased phenotype [58][59][60][61][62] . For example, endothelial differentiation of iPSC generated from diabetic mice displayed vascular dysfunction, impaired in vivo regenerative capacity, and diabetic iPSC displayed poor teratoma formation 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that these aberrant epigenetic changes may be partially overcome by genome-wide chemical treatments that restore some endothelial function 56,57 . The extent of retention of diseased diabetic epigenetic memory at developmental genes from incomplete or ineffective reprogramming within DhiPSC-derived lineages and its role in impaired regenerative capacity remains unclear, and marked by high variability in differentiation efficiency or retention of diseased phenotype [58][59][60][61][62] . For example, endothelial differentiation of iPSC generated from diabetic mice displayed vascular dysfunction, impaired in vivo regenerative capacity, and diabetic iPSC displayed poor teratoma formation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, endothelial differentiation of iPSC generated from diabetic mice displayed vascular dysfunction, impaired in vivo regenerative capacity, and diabetic iPSC displayed poor teratoma formation 63 . Human iPSC from patients with rare forms of diabetes-related metabolic disorders have similarly shown significant functional endothelial impairment 58 . Transient chemical demethylation of T1D-hiPSC was sufficient to restore differentiation in resistant cell lines and achieve functional differentiation into insulin-producing cells 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, iPSC‐derived cardiomyocytes from patients with T2DM recapitulated the T2DM cardiomyopathic phenotype allowing researchers to dissect the affected pathways . Additionally, iPSC‐derived endothelial cells have also proven to be an invaluable source to untangle the endothelial dysfunction associated with the disease …”
Section: Stem Cell Therapymentioning
confidence: 99%
“…[33] Additionally, iPSC-derived endothelial cells have also proven to be an invaluable source to untangle the endothelial dysfunction associated with the disease. [34] SCs also promise therapeutic potential. Labs around the world study SC-based applications for age-related macular degeneration (AMD), [28,35] spinal cord injury, [25,29,36] Parkinson's disease, [27,37] corneal diseases, [26,38] myocardial infarction, [39] aplastic anemia and leukemia associated with thrombocytopenia, [40] and demyelinating diseases such as multiple sclerosis, [41] as well as for cancer immunotherapies involving chimeric antigen receptor T (CAR-T) [42] and NKT cells.…”
Section: Stem Cell Therapy Nowmentioning
confidence: 99%
“…For example, endothelial differentiation of iPSC generated from diabetic mice displayed vascular dysfunction, impaired in vivo regenerative capacity, and diabetic iPSC displayed poor teratoma formation 63 . Human iPSC from patients with rare forms of diabetes-related metabolic disorders have similarly shown significant functional endothelial impairment58 . Transient chemical demethylation of T1D-hiPSC was sufficient to restore differentiation in resistant cell lines and achieve functional differentiation into insulinproducing cells18 .In summary, these studies have demonstrated that highly functional N-VP cells can be generated independent of genetic background or diseased origin from a diseased N-hPSC.Naïve reversion of conventional DhiPSC may potentiate an epigenetic remodeling of reprogrammed diabetic fibroblasts that avoided differentiation into dysregulated in dysfunctional ECs with 'diabetic epigenetic memory'.…”
mentioning
confidence: 99%